CAUSES OF DIVORCES IN ALBANIA - Molla, Alketa (European Scientific Journal, ESJ, 2015)
The statistics of divorce cases in Albania is very high compared to the number of population in the region. Various social and economic reasons have led to the separation of many Albanian families. Some of these reasons are related to immigration, which is a very widespread phenomenon in our society today. Some of the social causes of divorce include "coldness" in the couple’s relationships, adultery, ongoing conflicts between partners, and interventions from partners’ parents. Other social problem which is the major cause of divorce is using violence against women, or the excessive drinking habit of their spouse. Economic reasons for divorce include unemployment; the economic plight in which many families are, as a result of difficult economic conditions in the country; abuse of wives; lack of household income; and gambling. Due to the high level of unemployment in the country, many Albanians have chosen to immigrate. This is because they believed they will have the opportunity to gain employment and earn a good source of income. However, even when the economic status of the family has been improved, other problems still accompany divorce cases. In this article, I will be present some of the main factors which leads to divorce. The data of this study was obtained from the court statistics of Elbasan. The study included data obtained during the analysis of divorce files provided by the Office of the psychologist. The study was conducted in the region of Elbasan.